Association between birth weight, preterm birth, and nonalcoholic fatty liver disease in a community‐based cohort. Issue 5 (8th June 2022) - Amadou, Coralie; Nabi, Oumarou; Serfaty, Lawrence; Lacombe, Karine; Boursier, Jérôme; Mathurin, Philippe; Ribet, Céline; de Ledinghen, Victor; Zins, Marie; Charles, Marie‐Aline
Abstract: Background and Aims: The association between birth weight (BW) and metabolic outcomes has been described since the 1980s but NAFLD has been rarely studied. This study aimed to investigate the association between BW and NAFLD occurrence in adult subjects. Approach and Results: The study population consisted of participants from the French nationwide Constances cohort from 2012 to 2019. Participants with a history of chronic viral hepatitis or excessive alcohol consumption were excluded. Noninvasive diagnosis of NAFLD and fibrosis was performed using a combination of the Fatty Liver Index (FLI) and the Forns Index. The relationship between BW and NAFLD was analyzed with a sex‐stratified logistic regression model adjusted for sociodemographic parameters, lifestyle, and birth term, whereas liver fibrosis was analyzed with a sex‐stratified linear regression model. In total, 55, 034 individuals with reliable BW were included (43% men, mean age: 38 years). NAFLD (FLI ≥ 60) was present in 5530 individuals (10%). Multivariate logistic regression showed a significant U‐shaped relationship between BW and NAFLD, with no significant interaction with sex. A significant and slightly decreasing association was found between BW and Forns Index ( β  = −0.05; p  = 0.04). Premature birth (OR, 1.23; 95% CI, 1.03–1.48 for birth between 33 and 37 weeks versus ≥ 37 weeks) was associated with NAFLD, with a significant direct effect of premature birth, and without an indirect effect of low BW in mediation analysis. Forns Index was not significantly higher in participants with preterm birth compared to full‐term birth. Conclusions: This large prospective adult‐based cohort confirms the relationship between BW and NAFLD occurrence. Abstract :